PENGARUH INTENSITAS KUNJUNGAN PERPUSTAKAAN TERHADAP HASIL BELAJAR SISWA - Azaz Akbar (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2020)
Introduction. Finding ways to encourage student to learn is an effective way for social change. One institution that encourages students to enjoy learning independently is library. Purpose. This study aims to determine the relationship between the intensity of library visit and student’s learning outcome. The hypothesis of this scientific article is that there is a significant influence between the intensity of visiting school library and the learning outcomes of fourth grade students at State Elementary School 33 Buton in 2019/2020 Academic Year. Method. This type of research is quantitative research using three data collection techniques: test, questionnaire, and documentation. Results. The results of this study is data processing of two variables, the dependent variable, which is the intensity of library visit, and the independent variable, which is the student learning outcomes. This article also presents the results of linearity and hypothesis testing.